STRATEGI PEMBERDAYAAN UKM DALAM MENINGKATKAN KEUNGGULAN BERSAING PERUSAHAAN - Rati Afina Qurrata Ayun; Fitriyah Fitriyah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2019)
This study discusses the empowerment strategy of Small Medium Enterprise (SME) in the manufacturing sector at Ngingas Metal Industry Center, Kecamatan Waru, Kabupaten Sidoarjo, conducted by Dharma Bhakti Astra Foundation (YDBA) in increasing the company's competitive advantage. This research is a qualitative research to describe how empowerment is carried out to improve competitive advantage. The results of this study indicate an effort to integrate business and social activities where empowerment activities carried out benefits to the community and also affect the company's business strategy. Competitive advantage is achieved by optimizing one of the activities in the value chain, namely procurement activities. By making SMEs as suppliers, the company has alternative suppliers, guarantees the supply of inputs and gets more affordable prices of goods. Empowerment methods are carried out through training activities, mentoring, market facilitation and financing facilitation. The aim is that trained SMEs are qualified as suppliers and achieve self reliance.